Collimator Testing On Siemens X-Ray Mobile Unit At Radiology Installations K.R.M.T Wongsonegoro Semarang General Hospital - Kesawa Sudarsih; Nanik Suraningsih; Mega Indah Puspita (LPPM STIKES Guna Bangsa, 2018)
The quality control program includes several tests, including collimator testing. According to Kepmenkes No.1250 Year 2009, collimator testing is done once a month or after repair. Radiology Installation RSUD K.R.M.T Wongsonegoro Semarang, when examined baby gram and thoraks using aircraft X-ray mobile unit with wide field settings according to object size, the result of the resulting radiograph cut off. This X-ray plane was used in 2006. During the use, no collimator testing has been performed. This study aims to determine the results of the suitability of light beam collimator. His type of research is quantitative research with observational approach. This research uses Collimator Test Tool tool with variation of FFD 100 cm and 150 cm, the field of irradiation is set 14x18 cm. The test results were tabulated, then analyzed based on Kepmenkes No.1250 in 2009. Limit tolerance value of shift ≤ 2% of FFD used. The result of collimator test shows that in FFD 100 cm we get the average X axis = 1.38%, Y axis = 1.5%. FFD 150 cm obtained average X axis = 1.73%, Y axis = 1.42%. The value of the shift that occurs is still within the limits of tolerance. We recommend that you do a periodical test once a month to ensure the quality of radiography.